COMPARATIVE DENSITY FUNCTIONAL THEORY, DENSITY FUNCTIONAL TIGHT BINDING AND FORCE FIELD STUDIES OF AMINOACIDS, PEPTIDES AND PEPTIDE-TITANIA INTERFACES: BRINGING AB INITIO ACCURACY TO BIOMOLECULAR SIMULATIONS - LI WENXUAN (2016)
Master's